2008
DOI: 10.1074/jbc.m707576200
|View full text |Cite
|
Sign up to set email alerts
|

S-Phase-specific Activation of PKCα Induces Senescence in Non-small Cell Lung Cancer Cells

Abstract: Protein kinase C (PKC) has been widely implicated in positive and negative control of cell proliferation. We have recently shown that treatment of non-small cell lung cancer (NSCLC) cells with phorbol 12-myristate 13-acetate (PMA) during G 1 phase inhibits the progression into S phase, an effect mediated by PKC␦-induced up-regulation of the cell cycle inhibitor p21 Cip1 . However, PMA treatment in asynchronously growing NSCLC cells leads to accumulation of cells in G 2 /M. Studies in post-G 1 phases revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 52 publications
6
47
0
1
Order By: Relevance
“…There have been many reports of G0/G1 arrest in senescence (Kramer et al, 2001;Qian et al, 2008). However, it was also shown that senescence was accompanied by cell cycle arrest in G2/M arrest, including SP600125-induced G2/ M arrest (MacLaren et al, 2004;Mingo-Sion et al, 2004;Wada et al, 2004;Vigneron et al, 2005;Xia et al, 2006;Oliva et al, 2008). In this study, p21 has a major role in cell cycle arrest, and G2/M cell cycle arrest is associated with rapid CDC25 phosphorylation and decrease of cyclin B1 and CDK2 in SP600125-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of G0/G1 arrest in senescence (Kramer et al, 2001;Qian et al, 2008). However, it was also shown that senescence was accompanied by cell cycle arrest in G2/M arrest, including SP600125-induced G2/ M arrest (MacLaren et al, 2004;Mingo-Sion et al, 2004;Wada et al, 2004;Vigneron et al, 2005;Xia et al, 2006;Oliva et al, 2008). In this study, p21 has a major role in cell cycle arrest, and G2/M cell cycle arrest is associated with rapid CDC25 phosphorylation and decrease of cyclin B1 and CDK2 in SP600125-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 More recently, PKC-mediated induction of p21 WAF1/CIP1 was shown to be an obligatory event for PMA-induced senescence in non-small cell lung cancer cells. 20 In this study, we increase the knowledge of the mechanisms of PKC-mediated p21 induction and cell growth arrest by PMA. We show that exposure of H358 lung cancer cells to PMA increased the levels of the candidate tumor suppressor KLF6, which is downregulated in many lung cancer cell lines, concomitantly with an increase in the CDKI p21 WAF1/CIP1 .…”
Section: Methodsmentioning
confidence: 99%
“…1,20 This diverse range of effects is due to the opposing actions of various members or isozymes of the PKC protein family. 1,20 The induction of a putative tumor suppressor (i.e., KLF6) by PMA is not entirely expected because PMA is well known to act as a tumor promoting agent in two-stage carcinogenesis models (e.g., skin). 25,26 On the other hand, PMA or certain PKC activators induce cell growth arrest mediated by the cyclin dependent kinase inhibitor p21 WAF1/CIP1 .…”
Section: Methodsmentioning
confidence: 99%
“…PKC␦ was targeted against the following sense strands: 5Ј-CCAU-GAGUUUAUCGCCACC-3Ј and 5Ј-CAGCACAGAGCGUG-GGAAA-3Ј. The arrestin and PKC␣ siRNAs have been previously described (31,32). The PKC siRNAs were reconstituted individually at 60 pmol/l before transfection, and 300 pmol of each were combined for a total of 600 pmol/transfection.…”
Section: Methodsmentioning
confidence: 99%